Pengaruh Penerapan Sistem Manajemen Perkantoran terhadap Efisiensi Administrasi di Kantor Kementerian Agama Kabupaten Kutai Timur - Analisna Analisna; Faelasup Faelasup; Mukhtar Mukhtar (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
The implementation of office management systems in government agencies is one of the efforts to improve administrative efficiency. This study is motivated by the importance of the effectiveness of administrative work in the modern era, especially in the Office of the Ministry of Religious Affairs of East Kutai Regency. This study aims to determine how much influence the implementation of office management systems has on administrative efficiency. The method used is a quantitative approach with simple linear regression analysis. The population in this study was 40 respondents. The results showed that the office management system variable (X) had a positive effect on administrative efficiency (Y), with a correlation coefficient of 0.867 and a significant t-test value. The contribution of the office management system to administrative efficiency was 75.2%. Thus, the implementation of the office management system has a major impact on administrative efficiency, although there are other factors that also influence it. Therefore, improving the quality of office management, including document management, technology utilization, internal communication, and supervision, needs to be continuously developed to support optimal administrative services..